2023
DOI: 10.1002/jsfa.13100
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoleic acid‐rich oleaginous yeast Scheffersomyces segobiensis DSM 27193 exerts anti‐obesity effects by ameliorating hepatic steatosis and adipose tissue hypertrophy

Yujia Peng,
Lili Zhang,
Xinhui Bao
et al.

Abstract: BACKGROUNDYeast biomass, encompassing fatty acids, terpenoids, vitamins, antioxidants, enzymes, and other bioactive compounds have been extensively utilized in food‐related fields. The safety and potential bioactivities of Scheffersomyces segobiensis DSM 27193, an oleaginous yeast strain, are unclear.RESULTSScheffersomyces segobiensis DSM 27193 accumulated large palmitoleic acid (POA) levels (43.4 g kg−1 biomass) according to the results of whole‐cell components. We annotated the Kyoto Encyclopedia of Genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Obesity is characterized by the abnormal and excessive buildup of fat in adipose tissue, leading to an unhealthy condition, as outlined by the World Health Organization (WHO) [ 1 , 2 ]. The body mass index (BMI) of an individual is calculated by dividing their weight in kilograms by the square of their height in meters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is characterized by the abnormal and excessive buildup of fat in adipose tissue, leading to an unhealthy condition, as outlined by the World Health Organization (WHO) [ 1 , 2 ]. The body mass index (BMI) of an individual is calculated by dividing their weight in kilograms by the square of their height in meters.…”
Section: Introductionmentioning
confidence: 99%
“…The body mass index (BMI) of an individual is calculated by dividing their weight in kilograms by the square of their height in meters. A BMI score that falls within the range of 25 to 30 is categorized as being overweight or obese [ 1 , 2 , 3 ]. Based on the findings of the WHO’s report on obesity, it has been indicated that there are approximately 1.9 billion adults over the age of 18 who are classified as overweight, with an additional 600 million falling into the category of obesity.…”
Section: Introductionmentioning
confidence: 99%